The Relationship Between Family Satisfaction and Adolescents' Mental Health, Stress, and Depression - Eka, Angelina R; Bebok, Christin F.M; Iwa, Kornelia R; Natul, Fransiska Kurniati (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2025)
The family plays a crucial role in supporting the physical and psychosocial development of adolescents. This study employed a quantitative correlational approach to examine the relationship between family satisfaction and adolescents’ mental health status, stress, and depression. The research involved 205 adolescents aged 12–18 years in Ruteng, Manggarai, East Nusa Tenggara (NTT). Data were collected through questionnaires distributed to participants via Google Forms. The results showed significant relationships between family satisfaction and mental health status (p-value: 0.00), stress (p-value: 0.000), and depression (p-value: 0.000). The findings suggest that adolescents who experience family satisfaction tend to have better mental health. These results emphasize the vital role of the family in preventing mental health issues—especially stress and depression—among adolescents.